2018
DOI: 10.1080/14786419.2018.1471480
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, purification and antioxidant activity of novel polysaccharides from Dendrobium officinale by deep eutectic solvents

Abstract: Two novel polysaccharides DOP1-DES and DOP2-DES with molecular weight of 297,911 Da and 30,400 Da were extracted by using DESs from Dendrobium officinale for the first time, and purified with macroporous resin AB-8, Sephadex G75 and Sephadex G200 chromatography. Besides, the effect of extraction temperature, molar ratio of DES, reaction time and compound enzymes concentration on the extraction yield of polysaccharides were investigated. Monosaccharide composition analysis showed DOP1-DES and DOP2-DES were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 14 publications
1
18
1
Order By: Relevance
“…This outcome revealed that the DCP obtained from fresh D. catenatum stems with TPP and ethanol precipitation was an acidic glucomannan, which was inconsistent with the results reported by He et al (27), Kuang et al (28), and Zhang et al (10). Liang et al (29) found that the two polysaccharides (DOP1-DES and DOP2-DES) obtained from D. officinale stem via deep eutectic solvents were both mannoglucans comprising by Glc and Man in the percentages of 2.2:1.0 and 3.7:1.0, respectively. This finding was different from the above-mentioned data.…”
Section: Results and Discussion Physicochemical Properties And Chain Conformation Of Dcpcontrasting
confidence: 59%
See 1 more Smart Citation
“…This outcome revealed that the DCP obtained from fresh D. catenatum stems with TPP and ethanol precipitation was an acidic glucomannan, which was inconsistent with the results reported by He et al (27), Kuang et al (28), and Zhang et al (10). Liang et al (29) found that the two polysaccharides (DOP1-DES and DOP2-DES) obtained from D. officinale stem via deep eutectic solvents were both mannoglucans comprising by Glc and Man in the percentages of 2.2:1.0 and 3.7:1.0, respectively. This finding was different from the above-mentioned data.…”
Section: Results and Discussion Physicochemical Properties And Chain Conformation Of Dcpcontrasting
confidence: 59%
“…Signals near 1,387, 1,245, and 1,063 cm −1 were separately related to bending vibration of C-H group, and stretching vibrations of C-O and C-O-C groups. The characteristic absorption peaks at ∼953, 886, and 808 cm −1 indicated that the DCP had the α-and β-configurations of Man and Glc in pyranose sugar forms, respectively (29).…”
Section: Results and Discussion Physicochemical Properties And Chain Conformation Of Dcpmentioning
confidence: 99%
“…Several lines of evidence demonstrated that Dendrobium officinale polysaccharides (DOPs) exhibit antiinflammatory activities, regulate immunity and antioxidant and antitumor activities, etc. [6,7]. Gradually, polysaccharides in herbal medicines, including DOPs, have attracted much attention because of their antitumor activities with no significant side effects [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the combination of enzyme activity and the extractant power of DES, the so-called DES-based EAE, has been described as a promising alternative strategy for the extraction of polysaccharides from natural matrices due to their higher enzymecompatibility than the cellulose-dissolving ILs. Liang et al [69] Moreover, the use of specific enzymes for the selective removal of carbohydrates can also be found in the literature [70,71]. Recently, Aquino et al [72] obtained fractions enriched in oligosaccharides from goat colostrum (COS) by the enzymatic hydrolysis of lactose by an Aspergillus oryzae lactase prior to a concentration process with membranes.…”
Section: Enzyme-assisted Extractionmentioning
confidence: 99%